Blood sampling via a peripheral artery catheter decreases cerebral oxygenation index in very low‐birthweight infants. (7th October 2014) - Mehler, Katrin; Nowak, Mareike; Oberthuer, André; Hahn, Moritz; Roth, Bernhard; Kribs, Angela
Abstract Aim This study evaluated the impact of blood sampling via peripheral arterial catheters on cerebral oxygenation and blood volume as a function of blood sampling velocity. Methods Near‐infrared spectroscopy was applied to 20 very low‐birthweight infants during peripheral arterial blood sampling. Changes in cerebral oxygenated, deoxygenated and total haemoglobin, cerebral blood volume and cerebral oxygenation index were recorded. Heart rate and oxygen saturation were measured continuously. To assess the impact of blood sampling velocity, both fast 40‐sec and slow 70‐sec sampling procedures were performed in a crossover study design, in which the order of sampling velocities was randomised for each patient. Results Both fast and slow blood sampling procedures resulted in a significant decrease in cerebral oxygenation index (fast, p = 0.002, slow, p = 0.008), and an increase in mean heart rate (both p = 0.02) and mean blood pressure (p = 0.02 and 0.04). Oxygenated and total haemoglobin and cerebral blood volume only decreased significantly after slow blood sampling (p < 0.001). Conclusion Blood sampling from peripheral arterial catheters leads to significant fluctuations in cerebral oxygenation independent of the sampling velocity. Changes are comparable to those reported from umbilical blood sampling. We advise that blood sampling should be restricted as much as possible.